2018
DOI: 10.1155/2018/3804979
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Damage in Ischemia‐Reperfusion Injury: An Obstacle in Acute Ischemic Stroke after Revascularization Therapy

Abstract: Acute ischemic stroke is a common cause of morbidity and mortality worldwide. Thrombolysis with recombinant tissue plasminogen activator and endovascular thrombectomy are the main revascularization therapies for acute ischemic stroke. However, ischemia-reperfusion injury after revascularization therapy can result in worsening outcomes. Among all possible pathological mechanisms of ischemia-reperfusion injury, free radical damage (mainly oxidative/nitrosative stress injury) has been found to play a key role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
325
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 389 publications
(329 citation statements)
references
References 209 publications
(166 reference statements)
1
325
0
3
Order By: Relevance
“…Studies have shown that brain RAS triggers chronic inflammation leading to the release of ROS and inflammatory mediators through activating glial cells (Carvalho and Moreira, 2018). Uncontrolled effects of these mediators upregulate various inflammatory cascades resulting in cognitive dysfunction and neurodegeneration (Sun et al, 2018;Martire et al, 2015).…”
Section: Neuro-inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that brain RAS triggers chronic inflammation leading to the release of ROS and inflammatory mediators through activating glial cells (Carvalho and Moreira, 2018). Uncontrolled effects of these mediators upregulate various inflammatory cascades resulting in cognitive dysfunction and neurodegeneration (Sun et al, 2018;Martire et al, 2015).…”
Section: Neuro-inflammationmentioning
confidence: 99%
“…Ang II is considered as the main instigator that leads to the release of ROS and inflammatory mediators in neurodegenerative diseases (Chen et al, 2016). Ang II induced inflammatory cascades result in cognitive dysfunction and neurodegeneration in the brain (Sun et al, 2018;Martire et al, 2015). On the other hand, decreased amount of ACE2 and Ang (1-7) damages cells in cerebral arteries and enhances the level of oxidative stress (Peña Silva et al, 2012).…”
Section: Neuroprotectionmentioning
confidence: 99%
“…Stroke is the second leading cause of death and one of the leading causes of disability worldwide . Among all possible pathological processes occurring after ischemic stroke, free radical damage and oxidative stress have been found to play a key role in stroke . There is an increasing amount of experimental evidence that oxidative stress is a causal, or at least an ancillary factor in the neuropathology of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral ischemia-reperfusion (I/R) injury is proposed to be one of the most common complications following recanalization. 2,4 MicroRNAs (miRNAs) are endogenous approximately 23 nucleotides conserved RNAs that play important generegulatory roles, which may serve as diagnostic and prognostic markers due to their easy detection and stability in peripheral blood. 5 Evidence from experimental studies implicated multiple miRNAs participate in the response to I/R injury and hypoxic/ischemic events.…”
Section: Introductionmentioning
confidence: 99%